Preclinical Test Methods with Animal Mouse and Rats Biomedical Research: Technical Guideline - Rachmat Hidayat; Patricia Wulandari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
A B S T R A C TTrials in pre-clinical trials are very complex multidisciplinary studies. Extrapolatingdata from animals to humans requires information from many fields of science. Frompre-clinical trials, more detailed information and data on efficacy and safety wereobtained, especially at doses equivalent to doses in humans, and the presence orabsence of cumulative effects and whether these effects could return to normal(reversible) after the administration of the test material was stopped. This test canbe used to predict the negative impact on humans if he is exposed to the materialfor a long time.